2016
DOI: 10.3389/fpsyt.2016.00067
|View full text |Cite
|
Sign up to set email alerts
|

Functional Implications of the CLOCK 3111T/C Single-Nucleotide Polymorphism

Abstract: Circadian rhythm disruptions are prominently associated with bipolar disorder (BD). Circadian rhythms are regulated by the molecular clock, a family of proteins that function together in a transcriptional–translational feedback loop. The CLOCK protein is a key transcription factor of this feedback loop, and previous studies have found that manipulations of the Clock gene are sufficient to produce manic-like behavior in mice (1). The CLOCK 3111T/C single-nucleotide polymorphism (SNP; rs1801260) is a genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 55 publications
(59 reference statements)
0
31
0
1
Order By: Relevance
“…The SCN regulates the biological rhythms of the organism with oscillations in a 24‐hour cycle caused by self‐sustaining loops and self‐regulated transcription/translation of the so‐called circadian genes. The molecular machinery of the CR comprises > 20 circadian genes, the main components being the Clock circadian regulator ( CLOCK gene), Aryl hydrocarbon receptor nuclear translocator like ( ARNTL gene), Period circadian regulator ( PER 1, 2 and 3 gene), Cryptochrome circadian regulator ( CRY 1 and 2 gene) . Briefly, the CLOCK‐ARNTL protein complex stimulates expression of PER ( 1 , 2 and 3 ) and CRY ( 1 and 2 ), which are negative regulators of the CR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SCN regulates the biological rhythms of the organism with oscillations in a 24‐hour cycle caused by self‐sustaining loops and self‐regulated transcription/translation of the so‐called circadian genes. The molecular machinery of the CR comprises > 20 circadian genes, the main components being the Clock circadian regulator ( CLOCK gene), Aryl hydrocarbon receptor nuclear translocator like ( ARNTL gene), Period circadian regulator ( PER 1, 2 and 3 gene), Cryptochrome circadian regulator ( CRY 1 and 2 gene) . Briefly, the CLOCK‐ARNTL protein complex stimulates expression of PER ( 1 , 2 and 3 ) and CRY ( 1 and 2 ), which are negative regulators of the CR.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of BD are serious and include unusual changes in mood, energy metabolism, activity levels and the ability to perform activities of daily living . BD places substantial burdens on society due to a greater loss of productivity in BD patients when compared to patients with other mood disorders . Because it is a serious, chronic, disabling and common mental disorder, affecting 1%‐3% of the US population (for a review, see Geoffroy et al), understanding of its pathophysiological mechanisms, diagnostic forms and therapeutic interventions has increasingly been sought, although, the heterogeneous, episodic and recurrent nature of BD poses challenges for diagnosis and treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Clock knockout has allowed the identification of the functional consequences of some polymorphisms in the genes that regulate the molecular pathways of circadian rhythms. In the case of Per1 (one of the CLOCK genes), the variant 3111T/C alters transcriptional efficiency and therefore the physiological processes that control sleep-wake dynamics, body temperature, and the hormonal changes related to the molecular clock (Ozburn, et al 2016). …”
Section: Animal Modelsmentioning
confidence: 99%
“…The molecular basis for the circadian clocks consists of a family of proteins that function together in a transcriptional–translational feedback loop with the CLOCK protein as a key transcription factor of this loop 12 . A recent study showed that the CLOCK 3111C SNP resulted in higher expression of CLOCK and also increased the expression of PER2 — a transcriptional target of CLOCK 13 , suggesting a functional role of the genetic variant in the circadian control and, thus, altered circadian/daily rhythms of behavior and physiology in human C carriers.…”
Section: Introductionmentioning
confidence: 99%